Determination of generalized vibration table forces (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article determines the generalized forces of the technological set of equipment for concrete products production (vibrating table), in which the vibration exciter is fixed on the lever vertically in the center under the vibrating plate. This equipment is used for the manufacture of small-sized concrete products. Methods of mathematical physics and physical and mathematical modeling by methods of applied mechanics were used in the research. To determine the position and describe the free motions of the material bodies that make up the mechanical system under consideration, an orthogonal vibrational reference system of three coordinate systems was used. As a result, seven generalized forces acting on this mechanical system were determined. The obtained dependencies for the generalized forces will be used to compose a mathematical model of the above-mentioned equipment using the Lagrange equations of the second kind
Keywords: vibrating table; lever; vibrator; unbalance; generalized force; mechanical system